Universities in Imperial Austria 1848–1918 : A Social History of a Multilingual Space - Surman, Jan (2018)
"Combining history of science and a history of universities with the new imperial history, Universities in Imperial Austria 1848–1918: A Social History of a Multilingual Space by Jan Surman analyzes the practice of scholarly migration and its lasting influence on the intellectual output in the Austrian part of the Habsburg Empire. The Habsburg Empire and its successor states were home to developments that shaped Central Europe's scholarship well into the twentieth century. Universities became centers of both state- and nation-building, as well as of confessional resistance, placing scholars if not in conflict, then certainly at odds with the neutral international orientation of academe.